Strategy for Improving The Performance of Assistant Expenditure Treasurers at Community Health Centers Within The Working Area of The Sukabumi City Health Office - Rosita Hamid, Eka; Rahman, Abdul; Gedeona, Hendrikus Triwibawanto; Nurliawati, Nita (Universitas Muhammadiyah Pontianak, 2026)
This study examines strategies to improve the performance of Assistant Expenditure Treasurers (BPP) at Community Health Centers under the Sukabumi City Health Office, where non-financial backgrounds and dual roles reduce reporting accuracy and timeliness. The study aims to formulate priority improvement strategies. A mixed-methods approach was applied using interviews, observations, document review, SWOT analysis, IFAS–EFAS matrices, and the Analytical Hierarchy Process (AHP). Results place the organization in Quadrant I (aggressive), prioritizing continuous financial coaching clinics, followed by integrated digital SOP development and BLUD-oriented restructuring. These strategies strengthen accountability, efficiency, and sustainable financial governance.